“Alas, Not Yours to Have”: Problems with Audience in High-Stakes Writing Tests and the Promise of Felt Sense - Peter H. Khost (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Expanding the applications of “felt sense” can help students become more aware of audience—a corrective to the a-rhetorical effects of standardized testing and the Common Core Standards.